A strain of Meyerozyma guilliermondii isolated from sugarcane juice is able to grow and ferment pentoses in synthetic and bagasse hydrolysate media - Martini, Cristina [UNESP]; Tauk-Tornisielo, Samia Maria [UNESP]; Codato, Carolina Brito; Bastos, Reinaldo Gaspar; Ceccato-Antonini, Sandra Regina (Springer, 2016)
The search for new microbial strains that are able to withstand inhibitors released from hemicellulosic hydrolysis and are also still able to convert sugars in ethanol/xylitol is highly desirable. A yeast strain isolated from sugarcane juice and identified as Meyerozyma guilliermondii was evaluated for the ability to grow and ferment pentoses in synthetic media and in sugarcane bagasse hydrolysate. The yeast grew in xylose, arabinose and glucose at the same rate at an initial medium pH of 5.5. At pH 4.5, the yeast grew more slowly in arabinose. There was no sugar exhaustion within 60 h. At higher xylose concentrations with a higher initial cell concentration, sugar was exhausted within 96 h at pH 4.5. An increase of 350 % in biomass was obtained in detoxified hydrolysates, whereas supplementation with 3 g/L yeast extract increased biomass production by approximately 40 %. Ethanol and xylitol were produced more significantly in supplemented hydrolysates regardless of detoxification. Xylose consumption was enhanced in supplemented hydrolysates and arabinose was consumed only when xylose and glucose were no longer available. Supplementation had a greater impact on ethanol yield and productivity than detoxification; however, the product yields obtained in the present study are still much lower when compared to other yeast species in bagasse hydrolysate. By the other hand, the fermentation of both xylose and arabinose and capability of withstanding inhibitors are important characteristics of the strain assayed.
Keywords: Xylose fermentation; Bagasse hydrolysate; Biomass; Ethanol; Xylitol